Numerical fatigue damage analysis of a variable speed Francis pump-turbine during start-up in generating mode. Issue 1 (1st September 2022) - Biner, Daniel; Alligné, Sebastien; Nicolet, Christophe; Dujic, Drazen; Münch-Alligné, Cécile
Abstract: Variable speed hydropower units offer a large spectrum of grid regulation services and may therefore contribute to the stability of future power supply systems. Full Size Frequency Converters (FSFC) already found real world application in Pumped Storage Hydropower Plants up to a rated power of 100 MW and are even considered scalable up to a few hundred MW. Apart from the extension of the power range and grid regulation capacities, the FSFC technology also provides new control possibilities during transient operations such as start-up in generating mode. Thus, harsh conditions with damaging impact on the hydromechanical components may be avoided by tuning the operating point trajectory in the start-up phase. In this paper, runner fatigue damage during start-up in generating mode of a 5 MW variable speed Francis pump-turbine prototype equipped with a FSFC is numerically analyzed. The fixed speed solution is compared to a variable speed solution following a BEP tracking control strategy. 1D hydraulic transient simulations provide boundary conditions for detailed 3-D CFD/FEA simulations. Full and reduced numerical domains are used and compared. The overall outcome of the present numerical study indicates an important reduction of partial damages using variable speed drives for turbine start-up manoeuvres.